Professional military instructor identity in the South African National Defence Force - Wagner, William John; van Putten, Sonja; Rauscher, Willem (Scientia Militaria - South African Journal of Military Studies, 2021)
In 2015, the chief of human resources at the South African National Defence Force(SANDF) ordered the improvement of the instructional quality and military ethos ofmilitary instructors. This article, based on a comprehensive study in this regard, reportson the perceptions of a sample of military instructors in the SANDF on the existenceof a construct, known as the professional military instructor identity and its effect onmilitary ethos and instructional quality. A qualitative approach was followed, using aninterpretivist/constructivist paradigm, involving data collection by means of a focusgroup discussion and expert interviews and using thematic networks analysis as dataanalysis method. A conceptual framework for the professional military instructoridentity, consisting of sub-identities, influencing factors and identifying indicators, wasconstructed. Findings suggest that the professional military instructor identity is notrecognised as a construct in the SANDF; however, the elements are known, althoughonly vaguely. The findings also support the view that this situation may have affectedthe current declining military ethos and instructional quality of military instructors. Itis concluded that the institutionalisation and popularisation of the professional militaryinstructor identity, as well as professional recognition of military instructors in theSANDF, could improve the current situation.